2019
DOI: 10.1161/strokeaha.118.024723
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Guide Catheter Is Beneficial in Endovascular Treatment Regardless of Mechanical Recanalization Modality

Abstract: Background and Purpose— Based on its mechanism, the use of balloon guide catheters (BGCs) may be beneficial during endovascular treatment, regardless of the type of mechanical recanalization modality used—stent retriever thrombectomy or thrombaspiration. We evaluated whether the use of BGCs can be beneficial regardless of the first-line mechanical endovascular modality used. Methods— We retrospectively reviewed consecutive acute stroke patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 20 publications
2
77
0
1
Order By: Relevance
“…This device was considered an independent predictor of the first-pass effect success rate from a single thrombectomy device as well as a predictor of recanalization success and optimal clinical outcomes. [15][16][17][18][19] Although it has been recommended as a routine adjuvant technique for stent retrieval by several studies, 5,20 considerable controversy exists, notably when the distal access catheter is used in conjunction with the stent retriever, which may facilitate distal aspiration and minimize the impact of the absence of a BGC. 6 BGCs were not available during the study in our center.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This device was considered an independent predictor of the first-pass effect success rate from a single thrombectomy device as well as a predictor of recanalization success and optimal clinical outcomes. [15][16][17][18][19] Although it has been recommended as a routine adjuvant technique for stent retrieval by several studies, 5,20 considerable controversy exists, notably when the distal access catheter is used in conjunction with the stent retriever, which may facilitate distal aspiration and minimize the impact of the absence of a BGC. 6 BGCs were not available during the study in our center.…”
Section: Discussionmentioning
confidence: 99%
“…However, the final successful recanalization rates noted both in the AT and SRT groups were not inferior to the results obtained when using a BGC. 15,16 Although results of one study indicated that the use of a BGC was significantly superior to the application of the distal access catheter, the higher baseline ASPECTS demonstrated lessfrequent ICA occlusions in the BGC group that could lead to significant bias of the results. 15 The median PRT in the AT group was significantly lower than that of the SRT group in the overall sample (P ¼ .001) and the PSM sample (P ¼ .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, due to the small size of the radial artery, 29,31,32 there is typically a limitation to the use of a 6-Fr sheath, which typically prevents the utilization of BGC shown to be more effective in MT than conventional guiding catheters in both stent-retriever (SR) and contact aspiration (CA) treatment modalities. 33 Second, navigating the aortic arch from the right TRA requires different skills than those required when navigating the same vessels from TFA. A significant learning curve is required and a cut-off of 30 to 50 procedures has been proposed for the full optimization of procedural performance.…”
Section: Transradial Accessmentioning
confidence: 99%
“…In a recent meta-analysis, patients treated with a balloon guide catheter for mechanical thrombectomy showed higher odds of first-pass recanalization (odds ratio [OR], 2.1; 95% confidence interval [CI], 1.7–2.6) and modified Rankin Scale 0–2 (OR, 1.84; 95% CI, 1.5–2.2) compared to non-balloon guide catheter group [1]. Baek et al [2] investigated the effect of the balloon guide catheter not only in mechanical thrombectomy but also in aspiration thrombectomy. The balloon guide catheter group demonstrated significantly higher successful recanalization rate (87%) and higher first-pass recanalization rate (37%) compared to those of non-balloon guide catheter group (75% and 14%, respectively; P<0.001 each).…”
mentioning
confidence: 99%